Investigation of the atypical FBXW7 mutation spectrum in human tumours by conditional expression of a heterozygous propellor tip missense allele in the mouse intestines. Issue 5 (15th May 2013) - Davis, Hayley; Lewis, Annabelle; Behrens, Axel; Tomlinson, Ian
Abstract : Objective: FBXW7 encodes the substrate recognition component of a ubiquitin ligase that degrades targets such as Notch1, c-Jun, c-Myc and cyclin E. FBXW7 mutations occur in several tumour types, including colorectal cancers. The FBXW7 mutation spectrum in cancers is unusual. Some tumours have biallelic loss of function mutations but most have monoallelic missense mutations involving specific arginine residues at β-propellor tips involved in substrate recognition. Design: FBXW7 functional studies have generally used null systems. In order to analyse the most common mutations in human tumours, we created a Fbxw7 fl(R482Q) /+ mouse and conditionally expressed this mutation in the intestines using Vill -Cre. We compared these mice with heterozygous null ( Fbxw7 +/− ) mutants. Results: A few sizeable intestinal adenomas occurred in approximately 30% of R482Q/+ and Fbxw7 +/− mice at age >300 days. Breeding the R482Q allele onto Apc mutant backgrounds led to accelerated morbidity and increased polyp numbers and size. Within the small bowel, polyp distribution was shifted proximally. Elevated levels of two particular Fbxw7 substrates, Klf5 and Tgif1, were found in normal intestine and adenomas of R482Q/+, R482Q/R482Q and Fbxw7 −/− mice, but not Fbxw7 +/− animals. On the Apc mutant background, Fbxw7 +/− mutants had a phenotype intermediate between Fbxw7 wild-type and R482Q/+ mice. Conclusions: Heterozygous Fbxw7 propellor tip (R482Q) mutations promote intestinal tumorigenesis on an Apc mutant background. Klf5 and Tgif1 are strong candidates for mediating this effect. Although heterozygous null Fbxw7 mutations also promote tumour growth, these have a weaker effect than R482Q. These findings explain the FBXW7 mutation spectrum found in human cancers, and emphasise the need for animal models faithfully to reflect human disease.